The Strategic Role of Land Power on NATO’s Northern Flank - Wegge, Njord (Arctic Review on Law and Politics, 2022)
The debate about how to defend NATO’s northern flank is closely connected to geographic particularities, the demanding Arctic climate, as well as to ever-evolving technological developments. This research article aims at investigating the role land power plays in this region, with a special focus on northern Norway. Through investigating how structure and composition of land forces matter at the political-strategic level, as well as the role played by allied land forces in Northern Norway, this article seeks to better connect the ongoing debate about the structure of land forces in northern Norway to the political-strategic level. The article seeks to answer the research question by using historical sources and official military documents, as well as qualitative interviews.